Complete mitogenome sequence of Rasbora argyrotaenia (Actinopterygii: Cyprinidae) - Wahyu Endra Kusuma; Pratama Deffi Samuel; Dewa Gede Raka Wiadnya; Anik Martinah Hariati; Yoshinori Kumazawa (Mitochondrial DNA. Part B. Resources, 2017)
The mitochondrial genome of a small freshwater fish Rasbora argyrotaenia from Java Island, Indonesia, was completely sequenced. This mitochondrial genome had 16,740 bp in length and consisted of 37 genes in the typical vertebrate mitochondrial gene arrangement. Phylogenetic analysis showed that R. argyrotaenia is more closely related to R. borapetensis than to other Javanese rasboras, R. aprotaenia and R. lateristriata.